Beyond the Basics: Taxonomic Classification and Pathogenomics in Recently Discovered Dickeya dadantii Isolates - Mateus Sudario Pereira; Diego Lucas Neres Rodrigues; Juan Carlos Ariute; Douglas Vinícius Dias Carneiro; Pedro Alexandre Sodrzeieski; Marco Aurélio Siqueira Gama; Elineide Barbosa de Souza; Vasco Azevedo; Bertram Brenig; Ana Maria Benko-Iseppon; Flavia Figueira Aburjaile (Taxonomy)
The genus Dickeya consists of Gram-negative bacteria capable of causing soft rot symptoms in plants, which involves tissue breakdown, particularly in storage organs such as tubers, rhizomes, and bulbs. These bacteria are ranked among the top ten most relevant phytopathogens and seriously threaten economically valuable crops and ornamental plants. This study employs a genomic analysis approach to taxonomically classify and characterize the resistome and virulome of two new strains, CCRMP144 and CCRMP250, identified as Dickeya dadantii. These strains were found to be the causative agents of soft rot symptoms in chili pepper (Capsicum spp.) and lettuce (Lactuca sativa), respectively, in the northeastern region of Brazil. The methodology employed in silico techniques, including tetra correlation search (TCS) and Average Nucleotide Identity (ANI) analysis, in association with a phylogenomic tree inference. TCS and ANI analysis showed that the studied strains belong to the Dickeya dadantii species. The phylogenomic analysis grouped the studied strains in the D. dadantii clade. The genomic characterization demonstrates 68 virulence genes, 54 resistances of biocide and heavy metal genes, and 23 antibiotic resistance genes. As far as we know, this is the first genomic study with Brazilian D. dadantii strains. This study demonstrates the efficacy to taxonomic classification and provides insights into the pathogenesis, host range, and adaptability of these strains which are crucial for the development of more effective management and control strategies for soft rot diseases.